Modelling of the head and cervical spine in biomechanical analysis - Labar, Josip (Array, 1990)
The description of the human head and neck figure in motion is a very important part of biomechanical analysis of the complete human motion or some sequences of subject motion. In such current method it is often necessary to use mass moments of inertia as a part of the fundamental dynamic anthropomeasures when describing this motion. The work offers the new model for calculating mass moments of inertia of the head and neck for males and females, about the principle axis of inertia, with origin in the tenth rib midspine and second cervical, then horizontal line passing supersternal seam. The results are given in presented tables, which are comparable with the results of other authors. The graphical presentation of selected anthropomeasures against the percentage distribution values of male and female subjects is also given